HIV signaling through CD4 and CCR5 activates Rho family GTPases that are required for optimal infection of primary CD4+ T cells. Issue 1 (December 2017) - Lucera, Mark; Fleissner, Zach; Tabler, Caroline; Schlatzer, Daniela; Troyer, Zach; Tilton, John
Abstract Background HIV-1 hijacks host cell machinery to ensure successful replication, including cytoskeletal components for intracellular trafficking, nucleoproteins for pre-integration complex import, and the ESCRT pathway for assembly and budding. It is widely appreciated that cellular post-translational modifications (PTMs) regulate protein activity within cells; however, little is known about how PTMs influence HIV replication. Previously, we reported that blocking deacetylation of tubulin using histone deacetylase inhibitors promoted the kinetics and efficiency of early post-entry viral events. To uncover additional PTMs that modulate entry and early post-entry stages in HIV infection, we employed a flow cytometric approach to assess a panel of small molecule inhibitors on viral fusion and LTR promoter-driven gene expression. Results While viral fusion was not significantly affected, early post-entry viral events were modulated by drugs targeting multiple processes including histone deacetylation, methylation, and bromodomain inhibition. Most notably, we observed that inhibitors of the Rho GTPase family of cytoskeletal regulators—including RhoA, Cdc42, and Rho-associated kinase signaling pathways—significantly reduced viral infection. Using phosphoproteomics and a biochemical GTPase activation assay, we found that virion-induced signaling via CD4 and CCR5 activated Rho family GTPases including Rac1 and Cdc42 and led to widespread modification of GTPase signaling-associated factors. Conclusions Together, these data demonstrate that HIV signaling activates members of the Rho GTPase family of cytoskeletal regulators that are required for optimal HIV infection of primary CD4+ T cells.